AULA INVERTIDA Y SU INCIDENCIA EN EL PROCESO DE APRENDIZAJE EN ESTUDIANTES CON TRASTORNO DE HIPERACTIVIDAD. - ANGAMARCA GARCIA, OLFA SILVANA (2024)
The flipped classroom methodology, which involves the transfer of direct instruction outside the classroom and the application of knowledge inside, has been shown to have a significant impact on the learning process of students with hyperactivity disorder. This methodology offers key advantages for this specific group of students. First, it allows students to access learning material at their own time and pace, which can better suit each student's individual needs and learning style. This is especially beneficial for students with hyperactivity disorder, as they may have difficulty maintaining attention for long periods. By allowing them to review the material on their own time, you reduce the pressure and stress associated with needing to keep up with the pace of a traditional class. Additionally, the flipped classroom methodology encourages active interaction during class time. Instead of simply passively receiving information, students engage in hands-on activities, discussions, and problem solving that allow them to apply and deepen their understanding of the material. This active participation can help counteract the attention and concentration challenges faced by students with hyperactivity disorder, as they engage more directly and engaged with the content.